PERAN STAKEHOLDER DALAM KEBIJAKAN PENCEGAHAN PERNIKAHAN DINI DI KABUPATEN LOMBOK BARAT - Erlangga, Baba Dimas; Subowo, Ari; Herawati, Augustin Rina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Early marriage has developed into a multidimensional policy issue. West Lombok Regency is an area that has a high rate of early marriage in West Nusa Tenggara, but also has a commitment to preventing early marriage by issuing several policies. Regional Regulation Number 9 of 2019 concerning the Age of Marriage (PUP) is one of the policies issued early to reduce the rate of early marriage. This research aims to identify stakeholders and their roles, including factors that influence the implementation of stakeholders' roles in implementing policies to prevent early marriage in West Lombok Regency. This research uses a qualitative descriptive method by collecting data through observation, interviews and documentation. The research results show that the identified stakeholders in preventing early marriage in West Lombok Regency consist of the Regent, DPRD, Population Control, Family Planning, Women's Empowerment and Child Protection (DP2KBP3A), Education and Culture Service, Health Service, District Government, Village Government , Religious Affairs Office, NTB Child Protection Agency, SANTAI NGO (Yayasan Tunas Alam Indonesia) and Village Heads to the Community. Based on their influence and interests, these stakeholders are divided into Crowd, Context Setter, Key Players, and Subject. Meanwhile, the classification of stakeholders based on their roles is divided into Policy Creator, Implementor, Coordinator, Facilitator, and Acceletalor. Factors that influence the implementation of the stakeholder role include communication, resources, disposition and bureaucratic structure. The suggestions for this research are optimizing the role of regional governments, encouraging proportional budget allocations to prevent early marriage, and encouraging regional governments to build synergies with other stakeholders such as academics, the business world, and the media.